Effects of resistance plus aerobic training on body composition and metabolic markers in older breast cancer survivors undergoing aromatase inhibitor therapy - de Paulo, Thais R.S. [UNESP]; Winters-Stone, Kerri M.; Viezel, Juliana [UNESP]; Rossi, Fabricio E. [UNESP]; Simões, Regina R.; Tosello, Giuliano; Freitas, Ismael F. [UNESP] (Elsevier, 2018)
Objective: To evaluate the effects of combined aerobic + resistance training on body composition and metabolic markers in older breast cancer survivors undergoing aromatase inhibitor therapy. Methods: Older breast cancer survivors were randomized to an exercise [resistance + aerobic training]: n = 18, or placebo control group: n = 18. Body composition (measured by DXA) and blood markers of lipid and glucose were measured at baseline, and at 12, 24, and 36 weeks. The exercise group performed 40 min of resistance exercises on machines followed by 30 min of aerobic training on a treadmill, three times per week. Separate 2 (group) × 4 (time) repeated-measure ANOVAs were used to compare groups over time. Results: Significant group × time interactions were found for total and trunk fat mass (p < 0.001 and p = 0.001) and % body fat (p < 0.001), where women in the exercise group lost fat compared to slight gains among women in the stretching control group. There were no significant differences between groups for lean mass, hip or spine BMD, metabolic markers, or CRP. Conclusion: Our aerobic + resistance exercise program prevented fat gain, but may not have been sufficient to improve metabolic or bone health markers in older breast cancer survivors undergoing aromatase inhibitor therapy.
Keywords: Body composition; Cancer; Exercise training; Metabolic health; Physical activity